Sensitivity and scenarios of availability of water for human consumption in the micro watershed of Porrosati River, Heredia, Costa Rica - Montero-Sánchez, Esteban (2018)
Climate variability and land-use change represent two of the major constraints to the availability of water for human consumption in the future. With the aim of analyzing the availability of water for human use and consumption in the Porrosati Microbasin, water balances were calculated based on the groundwater recharge.  For estimates, meteorological records of 15 years (from 2000 to 2014) and analysis of the hydrological characteristics were used. To set up scenarios of water recharge in the medium (2026-2030) and long-term (2051-2055), taking into account scenarios of climate change, were used predictions of temperature and precipitation variation, developed by the National Meteorological Institute, under a scenario of emissions A2. The results obtained show atypical behaviors with significant changes in the seasonal behavior of recharge. Prospective volumes for the future show significant decreases that, in some cases, exceed the 15% on average, reaching up to 50% differences. In the long-term scenario, a major change is noticed in seasonal behavior, resulting in the emergence of two peaks of recharge.  The climate projections present a complex scenario with limitations to the water recharge of groundwater and, hence, the availability of water for human consumption in the medium and long-term.